Plasma concentration and eGFR in preterm and term neonates receiving gentamicin or successive amikacin therapy - Bonifasius Siyuka Singu; Milka Ndapandula Ndeunyema; Ene I. Ette; Clarissa Hildegard Pieper; Roger Karel Verbeeck (BMC, 2023)
Abstract Background Gentamicin and amikacin are aminoglycoside antibiotics which are renally excreted and known to be nephrotoxic. Estimate of glomerular filtration rate (eGFR) per body surface area is lower in neonates than in adults and exposure to these drugs could lead to more suppression in kidney function. The aim of this study was to determine maximum and minimum plasma concentrations (Cmax and Cmin), time to reach Cmin levels of gentamicin and amikacin, and to assess eGFR in preterm and term neonates. Methods Two groups of patients were recruited, 44 neonates receiving gentamicin (5 mg/kg/24 h) and 35 neonates receiving amikacin (15 mg/kg/24 h) by slow intravenous injection. Patients on amikacin had been on gentamicin before being switched to amikacin. Two blood samples were drawn for the determination of the maximum and minimum plasma concentration. Primary outcomes were determination of Cmax, Cmin, and the time it took to clear the aminoglycoside to a plasma concentration below the toxicity threshold (gentamicin: < 1 mcg/mL; amikacin: < 5 mcg/mL. Results Therapeutic range for Cmax of gentamicin (15-25 mcg/mL) or amikacin (30-40 mcg/mL) was achieved in only 27.3 and 2.9% of neonates, respectively. Percentage of neonates reaching plasma concentrations below the toxicity threshold within the 24-hour dosing interval was 72.7% for gentamicin and 97.1% for amikacin. Positive correlation between gentamicin clearance and postnatal age borderline statistical significance (p = 0.007), while the correlation between amikacin clearance and postnatal age was poor and not statistically significant (r2 = − 0.30, p = 0.971). Conclusion Although eGFR decreased significantly as a function of postnatal age in neonates receiving amikacin, the majority (91.4%) of these neonates were able to clear the drug to < 5 mcg/mL within a 24-hour dosing interval.